"Pecuária e Sustentabilidade: uma análise da produção de gado de corte em propriedades rurais no município de Paragominas, estado do pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2016)
Regulatory guidelines have in their policies the planning tool and transmutation of productive realities in man-environment relationship, making the market of the agricultural sector increasingly competitive and demanding as to reduce the impacts on climate, environment and society. The multiplicity of aspects involved delineate the transition to more sustainable production systems and dictate the pace of these changes. They also expose deep-rooted cultural traditions, technical and administrative deficiencies where individuals become synonymous with potentiation of economic matrix at the expense of social and environmental. Even before these contrasts the meaning of sustainability has been trivialized and used the favorable adjectives of agricultural production, whose practical realities in a broader context, not justify the positivism of marketing strategies. This case study aimed to evaluate the sustainability of beef cattle developed in properties located Paragominas, one of the Green Counties of Pará state. To this end, visits were undertaken in 17 properties taken as a reference in the region, of which collected productive, economic, social and environmental data with the help of special forms to characterize the producer profiles and landenvironmental production and properties. From the set of data indicators have been calculated, and established conformity in relation to the new sustainable guidelines based on Sustainable Livestock Working Group Criteria, chosen for its specificity and breadth policy. Both of them have been tabulated according to the categorized production systems. Emissions in GHGs and impacts on water resources were also estimated and perceptions of the main actors of the local livestock value chain recorded. The Barometer of Sustainability was the method of assessment used in both production level systems as the governing context. GHG emissions and impacts on water resources were calculated based on the methodology of the IPCC and Pereira (2012), respectively. The results showed that for the specific context of the production systems there was a concentration of properties ranging from the intermediate levels and potentially unsustainable. Increased the accuracy analysis for SFWG criteria, there was a downward migration to potentially unsustainable, and unsustainable levels, demonstrating the transience of any favorable status. Indicators of low productivity, profitability, costs efficiency, support of pasture capacity, recovery and job satisfaction were presented as recurring vulnerabilities in all systems analyzed. The environmental impacts demonstrate is proportional to the scale of production, coupled with the paradox that certain properties are fulfilling their social functions. The weak cohesion between the local livestock value chain agents is compounded by deficiencies of administration preventing the spread and consolidation of successful examples, as well as open space for practices focused on small groups of interests. Supported strategies for public-private partnerships, quality technical assistance and investments in Science, Technology and Innovation were recommended to overcome the specific disadvantages.
Keywords: Pecuária; Produção; Indicadores de Sustentabilidade; Clima; CNPQ::CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL::CRIACAO DE ANIMAIS